Relationship between central hemodynamic parameters and body composition and the functional state of neuro-autonomic regulation in young men - Krichfalushii, O. P.; Nemesh, M. I.; Slyvka, Ya. I.; Savka, Yu. M.; Palamarchuk, O. S.; Feketa, V. P. (Zaporozhye Medical Journal, 2024)
The aim of the study is to examine the relationship between central hemodynamic parameters and body composition by considering baseline functional state of neuro-autonomic regulation according to the index of regulatory system activity (IRSA) in young men. Material and methods. A total of 44 male participants were divided into three groups based on the IRSA level. The first group included 26 men with an optimal IRSA level. The second and third groups, each of 9 men, with moderate and high IRSA levels, respectively. The functional state of cardiovascular system was assessed using a device “REOKOM” (Kharkiv). The measurement of body composition was performed by weight-scale “TANITA BC-601” (Japan). The functional state of autonomic nervous system was assessed using a device “CARDIOLAB” (Kharkiv). Results. Our results have demonstrated higher hemodynamic parameters in men with moderate and high level of IRSA. Men with elevated level of sympathetic activity had the highest indices of the pumping function of the heart, and those with the balance between parasympathetic and sympathetic branches had the lowest indices of the pumping heart function. As for the indicators of total peripheral resistance and specific peripheral resistance, another trend was seen, namely, individuals with a balanced state of autonomic nervous regulation had the highest parameters, and those with a predominance of sympathetic tone had the lowest ones. Close correlations have been found between increased levels of regulatory mechanism tension and cardiohemodynamic parameters. An indicator analysis of the body component composition has revealed a significant increase in body mass index, total and visceral fat content in the examined groups with moderate and severe regulatory system tension. In addition, correlations have been found between IRSA and constituting components of body composition. Conclusions. The group assignment of the examined individuals according to IRSA has shown that a high tension of the regulatory mechanisms increased the load on the cardiovascular system, as indicated by higher indicators of central hemodynamics. In individuals with an optimal level of regulatory system functioning, the cardiovascular system activity is optimal and less energy consuming.